A prospective randomized comparative study of the efficacy of sustained release vaginal insert versus intracervical gel in primigravidae at term pregnancy - Thupakula, Thejaswi R.; Makhija, Bela; Haritwal, Arpana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
v Background: Induction of labour is the intentional initiation of labour before spontaneous onset for the purpose of delivery of fetoplacental unit. Failure of induction is responsible for increased incidence of caesarean delivery. This study performed to assess and compare the clinical effects of sustained release vaginal insert versus intracervical gel in primiparous women with term pregnancy in terms of improvement of Bishop’s score, Induction delivery interval, incidence of hyperstimulation, maternal and neonatal outcomes. Methods: A total 100 consecutive term pregnant women who underwent labor induction for fetal or maternal indications were divided randomly into two groups. Group A - sustained release Vaginal insert and Group B - Intracervical gel. Informed consent was taken from each patient. Results: Statistically significant increase in final Bishop’s score (p=0.008) and hyperstimulation (p=0.04) was seen in Vaginal insert group as compared to Intracervical gel group, while there were no statistically significant differences in maternal outcomes, neonatal outcomes and need for oxytocin augmentation in both groups. Conclusions: In this study we found that insert did not improve the induction delivery interval or rate of successful induction, nor did it have any advantage in terms of neonatal outcome although it did improve the Bishops score – Its advantage was in terms of single application, few prevaginal examinations, longer duration of action and immediate retrieval in case of hyperstimulation. Its main drawback remained the maintenance of cold chain without which its efficacy decreases. Another significant observation was the dropout rate of insert (16%).